Vibration Control of Tower Structure with Multiple Cardan Gyroscopes - Haoxiang He; Xin Xie; Wentao Wang (Shock and Vibration)
Tower structure is sensitive to hurricane and earthquake, and it is easy to generate large deflection and dynamic response. The multiple cardan gyroscope has two rotational degrees of freedom, which can generate strong moments to constrain the two horizontal orthogonal deflections if the rotor operates in high speeds, so the structural dynamic responses can be decreased. Hence, the method of dynamic control of the tower structure under wind load and earthquake action is proposed by using the multiple cardan gyroscopes as the dampers. The dynamic mechanism and the fixed axis principle of the multiple cardan gyroscope are introduced, and the dynamic equation of the gyroscope is established. The damping mechanism of the gyroscope is also described. For the tower structure equipped with the multiple cardan gyroscope dampers, the multidimensional control equation considering torsion effect is established, and the equivalent state space equation is presented. Taking a TV Tower with a number of gyroscope dampers as an analysis example, the structural dynamic responses and damping performance under fluctuating wind loads and earthquake action is studied. The results show that the multiple cardan gyroscope dampers with suitable parameters can effectively decrease the structural vibration in horizontal directions and torsional direction.